A Thioether‐Stabilized d‐Proline–l‐Proline‐Induced β‐Hairpin Peptide of Defensin Segment Increases Its Anti‐Candida albicans Ability. (20th June 2016) - Zhao, Bingchuan; Yang, Dan; Wong, Jack Ho; Wang, Jianpeng; Yin, Cuiming; Zhu, Yuxia; Fan, Shangrong; Ng, Tzi Bun; Xia, Jiang; Li, Zigang
Abstract: We report a β‐hairpin dual stabilizing strategy: ad ‐proline‐l ‐proline (d ‐Pro‐l ‐Pro) dipeptide as the nucleating turn, and a thioether tether as a side‐chain linkage at a precisely designed position to stabilize the β‐hairpin. This method was used to modify the C‐terminal β‐hairpin moiety of the plant defensin, pv‐defensin, in order to obtain a stabilized peptide with enhanced anti‐ Candida albicans activity (MIC 84–3.0 μm ), high serum stability (50 % remaining after 48 h) and low hemolysis (<10 % at 152 μm ). This modified peptide penetrated the C. albicans cell membrane within 5 min and showed high activity against clinically isolated antibiotic‐resistant C. albicans and Candida glabrata strains. Abstract : Using thed ‐Pro‐l ‐Pro dipeptide as the nucleating turn and a thioether tether as a side‐chain linkage can constrain peptides to the β‐hairpin conformation. We modified the C‐terminal β‐hairpin moiety of pv‐defensin, and obtained stabilized peptide with enhanced anti‐ C. albicans activity, high serum stability, and low hemolysis.